Traumatic Transitions: Homeless Women's Narratives of Abuse, Loss, and Fear. (May 2014) - Lewinson, Terri; Thomas, M. Lori; White, Shaneureka
This article presents traumatic experiences among 21 women residing in budget hotels after housing displacement. Framed in feminist and cumulative trauma theories, the purpose of this study was to explore types of trauma and adversity prior to and during housing at budget hotels. In this qualitative study, narrative and categorical content-analysis approaches were conducted to identify common themes across women's narratives. Findings revealed trauma narratives of physical and emotional abuse, childhood maltreatment, loss, financial exploitation, sexual intimidation, eviction anxiety, environmental stress, crime exposure, and systematic subjugation. Trauma-informed intervention approaches for social work practice are outlined to promote women's empowerment.